Mathematical modeling of voltage vectors measurement in the control systems of power-generating objects - Yakovlieva, I. V.; Tankevych, Ye. M.; Varskyi, H. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Mathematical model of error of tension vectors measuring channel is offered, that takes into account basic factors influencing the size of error, and can be used, in particular, for the calculation of amendments to the results of measuring with the purpose of their exactness increasement.